Identification and characterization of 1-hydroxypyrene contents in urine as a marker of exposure to pah in workers of electrolysis workshops at aluminum production - S.F. Shayakhmetov; A.N. Alekseenko; A.V. Merinov; O.M. Zhurba (Analiz Riska Zdorovʹû, 2022)
Potential harmful effects produced by highly toxic aromatic hydrocarbons (PAH) on health of workers employed at aluminum production make it necessary to identify biomarkers of exposure to the toxicants and to assess health risks.